1982
DOI: 10.2134/agronj1982.00021962007400040021x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tillage Practices on the Fertility Status of an Acid Soil Double‐Cropped to Wheat and Soybeans1

Abstract: Multiple cropping in conjunction with various minimum tillage practices is currently a conspicuous agricultural production method in the southeastern U.S. The objective of this study was to determine the influence of 5 years of various tillage practices on the fertility status of an Ultisol continuously double‐cropped to wheat (Triticum aestivum L.) and soybeans (Glycine max L.). The tillage treatments for each fall/spring were: no‐tillage/no‐tillage, harrow/ho‐tillage, conventional tillage/no‐tillage, no‐till… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
4
12

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 9 publications
7
32
4
12
Order By: Relevance
“…Greater (13) and lower (8,11) extractable K for no-tillage versus other tillage systems have been reported in surface horizons. Results of a three-year study on a coastal plain soil in Mississippi showed no K accumulation in the 0 to 5-cm depth with no-tillage compared to disking (14) and downward movement of K was also reported with this system.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Greater (13) and lower (8,11) extractable K for no-tillage versus other tillage systems have been reported in surface horizons. Results of a three-year study on a coastal plain soil in Mississippi showed no K accumulation in the 0 to 5-cm depth with no-tillage compared to disking (14) and downward movement of K was also reported with this system.…”
Section: Introductionmentioning
confidence: 96%
“…Surface lime application in no-tillage often does not ameliorate soil acidity deep within the profile due to limits in lime mobility (10,11). However, results from the only long-term study conducted in the coastal plain region that reported soil chemical properties demonstrated maintenance of soil pH at an acceptable level for crop production after eight years with no-tillage using surface application of lime (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em estudos realizados por HARGROVE et al (1982), também não foram observadas diferenças significativas em relação aos teores de cobre, extraído por DTPA, nas áreas sob semeadura direta e cultivo convencional.…”
Section: Introductionunclassified
“…Moreover, application of modern tillage methods decreases soil agitation, helps in conservation of soil humus, and prevents soil erosion (Hargrave et al 1982). Bonari et al (1995) studied the effect of using multi-task machines, as reduced tillage method, on the yield of crop or soil physical properties.…”
Section: Introductionmentioning
confidence: 99%